Foreign Aid and Market-Liberalizing Reform - Heckelman, Jac; Knack, Stephen (World Bank, Washington, DC, 2012)
Market-oriented economic policies-reflected in limited economic activity by government, protection of private property rights, sound monetary policy, outward orientation regarding trade and efficient tax and regulatory policy-have been strongly linked to faster rates of economic growth. Foreign aid is often provided in the belief that it encourages liberalizing reforms in these areas. This paper analyzes the impact of aid on market-liberalizing policy reform, correcting for the possible endogeneity of aid. Results indicate that higher aid slowed reform over the 1980-2000 period, as measured by a broad index of policies. Disaggregating policy into five areas, aid is significantly linked to slower reform in some policy areas but not in others. Disaggregating by decade, aid's adverse impact on policy reform is much more pronounced for the 1980s than for the 1990s.